Exploring the relationship between mental health disorders and medical compliance in patients with chronic diseases - Sharma, Poorti; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
The association between mental health conditions and chronic disease patients' adherence to their treatment plans is investigated in this study. Non-adherence to recommended medical treatments can worsen the progression of chronic conditions, which frequently call for long-term treatment plans. It is well known that mental health conditions such as stress, anxiety, and depression have a detrimental effect on patients' compliance with treatment plans and medical advice. The study looks at how patients' willingness and capacity to adhere to medical advice are influenced by things like the intensity of their symptoms, their mental health, and the support networks they have access to. To enhance medical compliance and general health outcomes in the management of chronic diseases, the study intends to draw attention to the necessity of integrated care approaches that address both mental and physical health through an analysis of patient interviews, clinical records, and treatment outcomes.